Field study on flow structures within aquatic vegetation under combined currents and small‐scale waves. Issue 4 (27th April 2021) - Zhang, Yinghao; Lai, Xijun; Ma, Jingxu; Zhang, Qian; Yu, Ru; Yao, Xin; Deng, Huanguang
Abstract: Field measurements were conducted to study the influence of aquatic vegetation on flow structures in floodplains under combined currents and wind‐driven waves. Wave and turbulent velocities were decomposed from the time series of instantaneous velocity and analysed separately. In the present study, the wind waves were small, leading to the ratios of wave excursion ( E w ) to stem spacing ( S ) for all cases tested here were less than 0.5. This caused the vertical distributions of time‐averaged velocity ( U horiz ) and turbulent kinetic energy ( TKE ) impacted by vegetation similar with the vegetated flow structures under pure current conditions. For emergent vegetation, U horiz and TKE distributed uniformly through the entire water column or increased slightly from bed to water surface. Similar distributions were present in the lower part of submerged vegetation. In the upper part of submerged vegetation, U horiz and TKE increased rapidly toward water surface and TKE reached its maximum near the top of vegetation. The measured wave orbital velocity ( U w ) fitted linear wave theory well through the entire water depth for both the emergent and submerged cases, so that with small E w / S the wave velocity was not attenuated within vegetation and U w within canopy can be predicted by the linear wave theory under combined currents and waves. However, wind‐driven waves made the turbulence generated near the top of canopy penetrate a deeper depth into vegetation than predictions under pure current conditions. Abstract : With small wave excursion relative to stem spacing (indicated as the weak wave‐plant interaction), vertical distributions of the time‐averaged horizontal velocity ( U horiz ) and the turbulent kinetic energy ( TKE ) influenced by vegetation under combined current and wave conditions were similar with that under pure currents. Turbulence generated near the top of canopy can penetrate a deeper depth into vegetation with the presence of waves than without. With weak wave‐plant interaction, the wave orbital velocity ( U w ) within vegetation was not significantly attenuated and can be predicted by the linear wave theory.